2017
DOI: 10.3389/fpsyg.2017.00855
|View full text |Cite
|
Sign up to set email alerts
|

The Affective Norms for Polish Short Texts (ANPST) Database Properties and Impact of Participants’ Population and Sex on Affective Ratings

Abstract: The Affective Norms for Polish Short Texts (ANPST) dataset (Imbir, 2016d) is a list of 718 affective sentence stimuli with known affective properties with respect to subjectively perceived valence, arousal, dominance, origin, subjective significance, and source. This article examines the reliability of the ANPST and the impact of population type and sex on affective ratings. The ANPST dataset was introduced to provide a recognized method of eliciting affective states with linguistic stimuli more complex than s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…Actual turnover or turnover intentions are negatively related to CSR; we hypothesize that incumbent employees appreciate their companies' CSR and are not willing to leave their socially responsible employer. The negative relationship of CSR and turnover intentions (e.g., Low et al, 2017 ; Wang et al, 2017 ) or actual turnover (e.g., Bode et al, 2015 ; Ng et al, 2019 ) has been reported several times, and identification mediated this relationship (Lee et al, 2008 ; Wang et al, 2017 ; Islam et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Actual turnover or turnover intentions are negatively related to CSR; we hypothesize that incumbent employees appreciate their companies' CSR and are not willing to leave their socially responsible employer. The negative relationship of CSR and turnover intentions (e.g., Low et al, 2017 ; Wang et al, 2017 ) or actual turnover (e.g., Bode et al, 2015 ; Ng et al, 2019 ) has been reported several times, and identification mediated this relationship (Lee et al, 2008 ; Wang et al, 2017 ; Islam et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…They could be referred to with words like vitally important, significant, turning-point, consequential, meaningful, and decisive. The scale appeared to be a reliable method – it provided stable and repeatable results – for assessing the subjective significance load of words ( Imbir, 2015 , 2016a ), sentences ( Imbir, 2016b , 2017b ), and music pieces ( Imbir and Goła̧b, 2017 ). In a recent study investigating the impact of arousal and subjective significance for modified performance in the EST ( Imbir, 2016c ), subjective significance reduced 1 the slowdown of reaction times caused by the arousal.…”
Section: Introductionmentioning
confidence: 99%
“…The studies for verbal materials [ 28 , 32 , 50 ], as well as music pieces [ 15 ], showed that the reliability (including split-half analyses as well as the stability of assessments) of origin and subjective significance SAM scales are comparable to the other SAM scales. All five SAM scales described above appeared to be useful tools for assessing aesthetic reactions to music and art [ 15 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%